2015
DOI: 10.1158/1535-7163.mct-14-0846
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide siRNA Screen Identifies the Radiosensitizing Effect of Downregulation of MASTL and FOXM1 in NSCLC

Abstract: Lung cancer is the most common cancer worldwide and on top of that has a very poor prognosis, which is reflected by a 5-year survival rate of 5% to 15%. Radiotherapy is an integral part of most treatment regimens for this type of tumor, often combined with radiosensitizing cytotoxic drugs. In this study, we identified many genes that could potentially be exploited for targeted radiosensitization using a genome-wide siRNA screen in non-small cell lung cancer (NSCLC) cells. The screen identified 433 siRNAs that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Recent evidence from a variety of model systems has shown that, besides its primordial role in mitotic division, Gwl also contributes in a significant extent to tumorigenic processes (Alvarez-Fernandez et al, 2017;Uppada et al, 2018;Vera et al, 2015;Dahlhaus et al, 2016;Nagel et al, 2015). Upregulation of Gwl activity promotes cell transformation and increases cell proliferation in several immortalized cells lines and in primary human fibroblasts (Vera et al, 2015).…”
Section: Gwl and Cancermentioning
confidence: 99%
“…Recent evidence from a variety of model systems has shown that, besides its primordial role in mitotic division, Gwl also contributes in a significant extent to tumorigenic processes (Alvarez-Fernandez et al, 2017;Uppada et al, 2018;Vera et al, 2015;Dahlhaus et al, 2016;Nagel et al, 2015). Upregulation of Gwl activity promotes cell transformation and increases cell proliferation in several immortalized cells lines and in primary human fibroblasts (Vera et al, 2015).…”
Section: Gwl and Cancermentioning
confidence: 99%
“…In breast cancer, MASTL expression increases with advanced clinical stage and predicts poor survival (Álvarez-Fernández et al, 2018;Rogers et al, 2018;Wang et al, 2016;Yoon et al, 2018), with high MASTL levels positively correlating with increased tumor growth and metastasis in vivo (Álvarez-Fernández et al, 2018;Rogers et al, 2018;Vera et al, 2015). Moreover, knockdown of MASTL induces radiosensitivity (Nagel et al, 2015), which makes MASTL an appealing pharmacological target. However, the exact mechanism of how MASTL facilitates tumorigenicity remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is a leading cause of cancer death worldwide, with a 5-year survival rate of 5–15% [1]. Non-small cell lung cancer (NSCLC), accounting for approximately 85% of all lung cancer cases, is the dominant type.…”
Section: Introductionmentioning
confidence: 99%